2022
DOI: 10.17358/ijbe.8.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Tourists’ Travel Experience Sharing on Social Media

Abstract: As travel-related content of tourist experiences benefits for both tourists to consume information online and for companies by providing insight into how visitors perceive their services, it becomes critical to understand the antecedents of travel experience sharing on social media. The study aims to develop a model of overall satisfaction, perceived enjoyment, motivations, and inhibitor toward sharing travel experiences, where personality factors impact overall satisfaction and perceived enjoyment. Partial Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This condition is in line with research conducted by Al-Htibat & Garanti (2019) that the more tourists are involved in the Cap Go Meh Singkawang festival, the higher the tendency to share information or experiences with other people. Likewise research that was conducted by Widiana & Novani (2022) also shows that customers who feel satisfaction at tourist attractions tend to share their experiences on social media. General attraction and culture attraction are also thought to have an indirect influence on the behaviour of sharing tourism experience.…”
Section: Introductionmentioning
confidence: 89%
“…This condition is in line with research conducted by Al-Htibat & Garanti (2019) that the more tourists are involved in the Cap Go Meh Singkawang festival, the higher the tendency to share information or experiences with other people. Likewise research that was conducted by Widiana & Novani (2022) also shows that customers who feel satisfaction at tourist attractions tend to share their experiences on social media. General attraction and culture attraction are also thought to have an indirect influence on the behaviour of sharing tourism experience.…”
Section: Introductionmentioning
confidence: 89%
“…Previous research has employed various fundamental theories to explain the antecedents of sharing experiences on SM, such as User and Gratification (Bakshi et al,2019;Hsu et al, 2020 in15;Li et al, 2022) Self-Determination Theory (Yuniawati, 2018;Septiari and Omar, 2022), Social Exchange Theory (OhandSyn, 2015), Social cognitive theory (Yen,2016), the Theory of Reasoned Action (Bilgihan et al, 2016), Social Influence Theory (Oliveira et al,2020). Other studies have examined the sharing motivations as individual constructs (Arica et al,2021;Widiana and Santi, 2022) or tried to distinguish between self-centered and community-related motivations (Munar and Jacobsen, 2014; Numerous studies have suggested that people share content on social media for one of two reasons. Firstly, they may be motivated by psychological needs, such as the desire for pleasure or recognition.…”
Section: Motivationsmentioning
confidence: 99%
“…Table 1 summarizes the main theories and motivations that have been examined in the context of sharing tourism experience. Furthermore, it has been found that customer satisfaction significantly affects consumer activity on social media SM such as e-WOM (Cantallops et al, 2020;Ismagilova et al, 2021;Xu et al, 2022) and sharing travel experience (Widiana and Santi, 2022). Sakiyama et al2023 explained this association in the light of three concepts.…”
Section: Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have witnessed a shift in what motivates tourists to choose their destinations, with contemporary travelers favoring places that enable self-expression on social media (Widiana & Novani, 2022). The rise of selfie tourism is particularly popular among both domestic and international tourists, indicating a changing landscape influenced by technology and the proliferation of social media platforms.…”
Section: Introductionmentioning
confidence: 99%